PHYSICIAN CONSCIENCE - Sweet, William (Science et Esprit, 2023)
In a number of jurisdictions in Europe and in North America, and particularly in Canada, the introduction and expansion of the conditions under which a patient may request euthanasia or assisted suicide – what is called, in Canada, ‘medical assistance in dying’ (MAiD) – has led to an increased concern about whether a physician may ethically refuse to perform such procedures – or, indeed, any legal medical procedure that lies within her practice. I argue that a physician may, sometimes, ethically refuse to perform such medical procedures. I begin with a clarification of some key terms: ‘acting on conscience’ (sometimes called conscientious objection), health, medicine, and ‘the duty of the physician.’ I then present some arguments to show that a physician is bound to provide medical care only under conditions entailed by or consistent with the aim of medicine. I consider some objections to this claim, and, then, show why these objections fail.